2020
DOI: 10.1111/acv.12663
|View full text |Cite
|
Sign up to set email alerts
|

Ecological niche modeling reveals manta ray distribution and conservation priority areas in the Western Central Atlantic

Abstract: The Western Central Atlantic (WCA) hosts a population of manta rays whose distribution and habitat preference is poorly understood. Addressing this lack of knowledge will be essential to aid the effective implementation of targeted conservation measures. Here, we use ensemble ecological niche modeling to predict the monthly distribution of manta rays in the WCA using multiple sources of species occurrence data, and consequently identify core areas, which represent suitable habitat in all months of the year. Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 75 publications
0
13
0
Order By: Relevance
“…Projecting species distributions in future climates remains an important avenue of research. Doing so can inform us of habitat potentially at risk from species invasions (Gong et al, 2020 ; Kistner‐Thomas, 2019 ), identify species at risk of collapse (Lemoine, 2015 ), and pinpoint regions of high priority for conservation (Garzon et al, 2021 ). In doing so, researchers must carefully account for source of uncertainty.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Projecting species distributions in future climates remains an important avenue of research. Doing so can inform us of habitat potentially at risk from species invasions (Gong et al, 2020 ; Kistner‐Thomas, 2019 ), identify species at risk of collapse (Lemoine, 2015 ), and pinpoint regions of high priority for conservation (Garzon et al, 2021 ). In doing so, researchers must carefully account for source of uncertainty.…”
Section: Discussionmentioning
confidence: 99%
“…ENMs correlate occurrence records with climate and are often used to predict range expansions. For example, ENMs can identify areas at risk of invasion under future climates (Gong et al, 2020 ; Kistner‐Thomas, 2019 ) or identify high‐priority conservation targets (Garzon et al, 2021 ), which is critically important as the ranges of many threatened species might collapse in the near future (Lemoine, 2015 ). One shortcoming is that ENMs rarely account for phenology (Ingenloff & Peterson, 2021 ); many simply use mean annual temperature or precipitation (Booth et al, 2014 ; Title & Bemmels, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…The spatio-temporal distribution of manta rays in the EUS is poorly understood. A recent study evaluated habitat suitability and regional hotspots for manta rays in the Gulf of Mexico and Caribbean 30 . This ecological niche model 30 was developed using presence-only data for putative manta ray sightings, and found that distributions were best predicted by chlorophyll-a and bathymetric slope, with minimal predictive input from sea surface temperature (SST).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study evaluated habitat suitability and regional hotspots for manta rays in the Gulf of Mexico and Caribbean 30 . This ecological niche model 30 was developed using presence-only data for putative manta ray sightings, and found that distributions were best predicted by chlorophyll-a and bathymetric slope, with minimal predictive input from sea surface temperature (SST). The authors noted that the majority of sightings were from coastal waters, potentially due to increased but unquantified survey effort 30 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation